Educação ambiental por meio de jogos e brincadeiras no ensino fundamental: uma análise de percepção e sensibilização ambiental com as crianças - Tavares, Antonio Gilmar Carvalho (2019)
Environmental Education (EE) is an important tool in change and construction of the attitude of the population, especially of children, in favor of a pro-environmental awareness, since, as a purpose, it offers information that encourages a better behavior and relationship between humanity, society and nature, motivating them to have a more responsible position in the environment. The study main objective was to evaluate the students perception of two municipal public schools in Lavras, MG, on the environment, and to develop EE activities throughout 2018. These activities aimed to stimulate awareness of the socio-environmental reality, as well as to instigate environmentally appropriate attitudes, values and behaviors. The project was developed during the school year, with students groups (children) from two public municipal schools. With the intention of obtaining an initial diagnosis about the students' perception about the environment, it was asked them to draw what is or what compounds the environment. Soon after this activity, it was applied an illustrative quiz with the same intention, which was replicated at the end of the project. In the course of the project activities, it was developed EE activities with these students, through dialogic lectures complemented with paintings of drawings, films, stories, lectures, debates and workshops, among other activities. In 2018, it was valued games and play as pedagogical elements in the activities development. We found that the activities were more enjoyable and motivational. This instigated the participation of the whole group. Besides that, the activities developed during the year had a positive impact on the changing perception of children about the environment.